Exploring the factors of achieving supply chain excellence: a New Zealand perspective. Issue 8 (11th June 2018) - Luo, Wen; Shi, Yangyan; Venkatesh, V. G.
Abstract: The objective of the paper is to analyse supply chain (SC) excellence from the practitioners' perspective in the New Zealand (NZ) context. The extant literature does not focus on achieving this excellence with the contemporary factors of this dynamic field. The study is an exploratory one using the structured Delphi technique to understand the ground level experience of the practitioners on the constructs of supply chain excellence. In this paper, we have administered three poll rounds to gather insights from the SC practitioners on the various enablers and barriers that impact supply chain excellence in the NZ environment. Seven supply chain management constructs are explored for their relationships with barriers and enablers in achieving the excellence in supply chains. The outcomes reveal that the people relevant issues (i.e. SCM knowledge education and supply chain culture) are more significant than other technical and operational factors. However, the influences from specific NZ business environment issues become far less important than a few years ago. This paper seeks the integration of practice-based views with the academic supply chain literature and original contributions from the NZ context.